Validity Analysis of Popular Scientific Books Fish Type Diversity as Environmental Material tor Vertebrate Zoology Course - Riya Irianti; Mahrudin Mahrudin (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2021)
Validation of teaching materials is needed to see the suitability of the teaching materials developed with learning outcomes, so that these teaching materials are suitable for use in learning. One type of written work that can be used as teaching material is popular scientific books. Popular scientific books are used by students to increase knowledge about the material being studied. The purpose of this study was to analyze the validity of the popular scientific book Diversity of Fish Species as Enrichment Material for Vertebrate Zoology Courses. Descriptive quantitative research method, to find information on the validity of popular scientific books compiled based on research results. The subjects of the validity data are 3 validators (expert judgment). Data were analyzed descriptively. The results showed that popular scientific books were compiled for aspects of coherence 95.8%, readability 83.3%, vocabulary 87.5%, active and passive sentences 100%, systematics 83.3%, writing method 100%, applications and implications 100 %, definitions and explanations 91.67%, and other styles of devices 87.5%. Based on the results of the study, the average validity score was 92.13% with a very valid category.Abstrak Validasi terhadap bahan ajar diperlukan untuk melihat kesesuaian antara bahan ajar yang dikembangkan dengan capaian pembelajaran, sehingga bahan ajar tersebut layak digunakan dalam pembelajaran. Salah satu jenis karya tulis yang dapat digunakan sebagai bahan ajar adalah Buku ilmiah popular. Buku ilmiah populer dimanfaatkan mahasiswa untuk menambah pengetahuan tentang materi yang dibelajarkan. Tujuan penelitian ini adalah menganalisis validitas buku ilmiah populer Keanekaragaman Jenis Ikan Sebagai Bahan Pengayaan Mata Kuliah Zoologi Vertebrata. Metode penelitian deskriptif kuantitatif, untuk menemukan informasi validitas buku ilmiah populer yang disusun berdasarkan hasil penelitian. Subyek data validitas yaitu 3 orang validator (expert judgement). Data dianalisis secara deskriptif. Hasil penelitian menunjukan bahwa buku ilmiah populer yang disusun untuk aspek koherensi 95.8%, keterbacaan 83,3%, kosa kata 87,5%, kalimat aktif dan pasif 100%, sistematika 83,3%, metode penulisan 100%, aplikasi dan implikasi 100%, definisi dan penjelasan 91,67%, serta gaya lain perangkat 87,5%. Berdasarkan hasil penelitian didapatkan untuk rerata skor validitas 92,13% dengan kategori sangat valid.